Effects of Cooking on Antioxidant Activities and Polyphenol Content of Edible Mushrooms Commonly Consumed in Thailand - Kettawan, Aikkarach; Chanlekha, Kunlaya; Kongkachuichai, Ratchanee; Charoensiri, Rin (Pakistan Journal of Nutrition, 2011)
The effect of boiling on ten edible mushroom varieties was analyzed for antioxidant activities by three different assays (ORAC, FRAP and DPPH) and polyphenol content. The results indicated that the boiling process significantly decreased both antioxidant activities and polyphenol content in all mushroom varieties. Antioxidant activities and the polyphenol content of boiled mushrooms can be ranked from high to low as A. hygrometricus > A. Cylindracea > V. volvacea > L. edodes > P. eryngii. Percent true retention of ORAC, FRAP, DPPH and polyphenol content in cooked tissue of all mushrooms ranged from 21-75%, 17-68%, 23-66% and 21-70%, respectively with the highest value in A. hygrometricus. Antioxidant activities and polyphenol contents were released into the cooking water was approximately 9-31%, 9-50%, 10-48% and 10-39% for ORAC, FRAP, DPPH and polyphenol, respectively. Percent loss of ORAC, FRAP, DPPH values and polyphenol content caused by thermal effect were about 9-64%, 8-60, 5-57% and 13-59%, respectively. Significantly positive correlations were observed between polyphenol and antioxidant activities in both raw and cooked mushrooms. The difference of characteristic structure and shape of each mushroom variety could affect the different loss of antioxidant activities and the polyphenol during the cooking process. Since mushrooms have been used as food and food flavoring material in soups for many years, consuming boiled mushroom tissues as well as their broths to recover some polyphenol and antioxidant activity is recommended.